The Career Effects of Union Membership - Samuel Dodini; Kjell G. Salvanes; Alexander Willén; Li Zhu; Alexander L.P. Willén (Center for Economic Studies and ifo Institute (CESifo), 2023)
We combine exogenous variation in union membership with detailed administrative data and a novel field survey to estimate the career effects of labor union membership. In the survey, we show how workers perceive the role of unions in setting wages and determining work amenities. In the administrative data, we causally examine through which channels unions influence worker outcomes, whether unions influence workers differently across their careers, and what the overall long-run effects of individual union membership are. Our results highlight that the career effect of union membership differs greatly depending on the age at which workers enroll. In addition, we show that focusing on a restricted set of outcomes, such as wages and employment, generates a fractionalized understanding of the multidimensional career effect that union membership has on workers.
Keywords: J51; J31; J32; J16; J63; J65; J81; 330; unions; wage premiums; job protection; work environment